INFLUENCE OF RESTING TONGUE POSTURE ON MANDIBULAR ARCH WIDTH AND VERTICAL DIMENSIONS OF FACE - Tariq, Qurat Ul Ain; Abdullah Jan; Neha Arshad; Zainab Binte Nazir (Journal of Postgraduate Medical Institute, 2023)
Objective: To evaluate the influence of tongue posture on the arch width of the mandible and the facial proportions in the vertical dimension. Methodology: A cross-sectional analysis was carried out utilizing lateral cephalograms and dental molds from 120 participants (45 males, 75 females). The participants were classified into three categories based on the dimensions of their vertical facial structure: Normodivergent, Hyperdivergent, and Hypodivergent. The posture of the tongue was ascertained by measuring the distance from the tongue to the palate using the technique introduced by Graber and colleagues. The widths of the mandibular dental arches were assessed using the study molds. Differences among the groups were evaluated using one-way ANOVA. Relationships between mandibular arch widths and six distinct tongue-to-palate measurements were investigated using Pearson's correlation. A p-value of< 0.05 was deemed to indicate a statistically significant result. Results: The comparison of the tongue to palate distances (D1, D2, and D3) at 0, 30, and 60 degrees among study groups showed statistically nonsignificant differences, however, the tongue to palate distances (D4, D5, and D6) showed statistically significant differences amongst all groups. Statistically significant differences were found in intercanine and intermolar width among the three study groups. The correlation of tongue posture with mandibular intercanine width and intermolar width at all six tongue-to-palate distances was weak. Conclusion: In hyperdivergent patients, the tongue posture was lower as compared to hypodivergent and norm divergent patients, especially at the mid-dorsum, anterior dorsum, and tongue tip regions. A weak correlation was found between mandibular arch width and tongue posture.